ISLAM DALAM KONTEKS PENGEMBANGAN MASYARAKAT MELAYU NELAYAN BAGIAN PERTAMA: POTRET KONDISI SOSIAL FAKTUAL DESA TAMERAN BENGKALIS RIAU - Arbi Yasin (Lembaga penelitian dan pengabdian kepada Masyarakat, 2016)
Temeran's fishing communities are mostly muslims malay. Tameran village has considerable potential of marine resources, but its people are still poor. The main focus of the study is a comprehensive study of the factual situation and social conditions, population, diversity of ethnic and religious groups, educational profile, system and community structure, management and management. The results of this research can be known that the Tameran villager has human resources with a formal education is still low. The Malay population who work as fishermen in the village of Tameran shares 187 people, consisting of: boat owner 18 people (9,6%), cano owner 42 people (22,5%), owner of pond 3 people (1,6%), As a fisherman laborer there are 80 people (42,8%) and others/working assistant of fisherman 44 people (23,5%). The community structure shows the pattern of